Excitations in organic solids - Agranovich, V. M. (Vladimir Moiseevich), 1929- (Oxford : Oxford University Press, 2009)
The work provides a detailed and uniform treatment of the science and technology of light absorbing organic materials (used in nano-scale optical devices, LEDs, solar cells, flat screens, cell phones etc), which are increasingly investigated for use in mass market products.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Exciton theory; Organic solid state chemistry; Nanostructured materials